Photocatalytic and adsorption property of ZnS–TiO/RGO ternary composites for methylene blue degradation - YL Qin; WW Zhao; Z Sun; XY Liu; GL Shi; ZY Liu; DR Ni; ZY Ma (Adsorption Science & Technology)
The visible light–driven ZnS–TiO 2 /RGO nanocomposites, with good visible light–driven photocatalytic activity, utilizing graphene oxide as precursor, were successfully synthesized via a facile solvothermal thermal method with graphene oxide as precursor. Ti 4+ ions were derived from titanium dioxide powder (TiO 2 , P25) and tetrabutyl titanate. S 2− ions and Zn 2+ ions were provided by sodium sulfide and zinc acetate, respectively. The photocatalytic and absorbance activity of the nanocomposites was investigated through the photocatalytic degradation of methylene blue in aqueous solution. The results showed that the ZnS–TiO 2 /RGO nanocomposite prepared by tetrabutyl titanate exhibited better photocatalytic and adsorbance activity for methylene blue under visible light irradiation and its photocatalytic efficiency reached 90% in 60-min light irradiation, almost 1.5 times that of the synthesized ZnS–TiO 2 /RGO by P25, which was attributed to a cooperative reaction because of an increase of photo-absorption effect of graphene sheets and photocatalytic effect of ZnS nanoparticles. The adsorbance activity for ZnS–TiO 2 /RGO–tetrabutyl titanate) reached 48%, which was almost 1.7 times higher than that of ZnS–TiO 2 /RGO-P25 and almost 3.7 times higher than that of ZnS/RGO.